ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA SMA PADA MATERI BARISAN DAN DERET ARITMATIKA - Rohmah, Hany Fathu; Warmi, Attin (IKIP Siliwangi, 2021)
Mathematics is a science that is structured and consists of integrated concepts. So in solving problems in mathematics, good mathematical connection skills are needed. The purpose of this study was to analyze and describe the mathematical connection abilities of high school students in the Arithmetic Sequences and Series material. This type of research used is a qualitative descriptive study with the research subjects being students of class XI in a high school in Bekasi Regency with a total of 30 students. Data collection techniques used in this study were interviews and tests, while the data analysis technique consisted of 3 stages, namely data reduction, data display and then a conclusion was drawn from the research results. From the results of the study, it is known that the mathematical connection ability of students on the connection indicator between mathematics and everyday life is obtained by a percentage of 70% which is in the medium category, on the indicator of the connection between concepts in one mathematics material and the inter-topic connection in mathematics obtained a percentage of 73% and has entered the high category, then the last indicator, namely the connection between mathematical material, namely arithmetic sequences and arithmetic series with other sciences, gets the highest percentage of other indicators, namely 84% and is in the high category. Overall the average mathematical connection ability of the students was in the high category.